Web Logs:The Current Online Information Sources - Mestri, Mamata; Kumbargoudar, Praveenkumar (Journal of Information and Knowledge, 2011)
Web logs are a recent technology in Information Communication. The present paper explains about Web logs. The information available in web logs is also discussed. There are different kinds of web logs based on their information content. The web logs are advantageous to the Library and Library professionals in providing Information Services. The paper discusses about the usefulness and advantages of Web logs to the Library.